Computation Cost Price of clinical laboratories services in valiasr hospitals in Tehran in 1387 by using of ABC model - A.A Nasiripoor; J Tabibi; M.R Maleki; T Nourozi (Tehran University of Medical Sciences, 2010)
Background: The most basic financial information and data which are needed for a laboratory manager is the costs allocated to the cost unit and the cost of services. The cost prime can increase the managers function in practical beget and strategies plan and this article based on function , is don to calculate the cost prim of clinical laboratories services in VALI A SR Hospital in Tehran by using of ABC model . Material & Methods: the study is a practical research done by descriptive-analytic method in a periodical and retrospective form during Forward to Esfand of 1378. Thirty tests were chosen according to the fluency chart. Data collecting tools, information sheets, interviews and direct observations were collected and analyzed and the cost price of laboratory services calculated by the help of MY ABCM software. Results: In VALI A SR Hospital's laboratory, Findings demonstrate that, maximum and minimum costs are related to human recourses cost (44%) and energy cost (.5%) also about activities, most activities is related to expertise activates(97% of total ). these result show THE importance of human recourses especially expert human recourse in prime cost. the maximum prime cost is related to urine analysis(11%) and the minimum prime cost is related to sodium an of biochemistry's group(21%). it means more frequency of services lead to reduce of services prime cost. Finally the average of calculated prime cost was different to hygiene ministry tariff (about 63%).this difference is result of unrealistic tariffs vs. prime cost of services.Conclusion: According to volume test operational and other conveniences in the Valia'asr hospital's laboratory, this laboratory encounter to missing budget. We can reduce the service's prime cost by improvement of performance management especially in human recourse filed and consume recourses in best way by standardization of consumption.